2010
DOI: 10.1016/j.bbadis.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of a novel identified TNFAIP8 family is associated with diabetic nephropathy

Abstract: Tumor necrosis factor-α-inducible protein 8 (TNFAIP8) family are very recently identified proteins which share considerable sequence homology to regulate cellular and immune homeostasis. However, it is unknown whether TNFAIP8 family is expressed in the kidney and contributes to the regulation of renal functions. Therefore, the present study was designed to characterize the members of TNFAIP8 family in the kidney and to explore their possible roles in the development and progression of diabetic nephropathy. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 37 publications
4
48
0
Order By: Relevance
“…32 TNFAIP8 expression is also increased in diabetic kidneys, and it is upregulated in mesangial cells in response to high glucose levels, with concordant mesangial cell proliferation enhancement. 33 Moreover, TNFAIP8 protein is known to be induced by NF-κB activation, 34 a central pro-proliferative, antiapoptotic transcription factor. 35 Mechanistic studies have shown that decreased TNFAIP8 expression led to concomitant decreases in the levels of vascular endothelial growth factor receptor-2 (VEGFR-2) and matrix metalloprotease (MMP) 1 and 9.…”
Section: Introductionmentioning
confidence: 99%
“…32 TNFAIP8 expression is also increased in diabetic kidneys, and it is upregulated in mesangial cells in response to high glucose levels, with concordant mesangial cell proliferation enhancement. 33 Moreover, TNFAIP8 protein is known to be induced by NF-κB activation, 34 a central pro-proliferative, antiapoptotic transcription factor. 35 Mechanistic studies have shown that decreased TNFAIP8 expression led to concomitant decreases in the levels of vascular endothelial growth factor receptor-2 (VEGFR-2) and matrix metalloprotease (MMP) 1 and 9.…”
Section: Introductionmentioning
confidence: 99%
“…In addition and among other problems, diabetic patients are more likely to develop obesity [13][14][15][16], coronary heart disease, stroke [17][18][19], diabetic nephropathy [20][21][22][23], diabetic retinopathy [24][25][26][27] and diabetic neuropathy [28][29][30][31]. These diseases are largely responsible for the observed high mortality rates in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…TIPE2 can regulate both inflammation and carcinogenesis (8,11) Interestingly, it is found highly expressed in macrophages and serves as a negative regulator of innate immunity through inhibiting TLR signaling (8,12,13). Its germline deletion leads to fatal inflammatory diseases, and abnormal expression of TIPE2 in humans was found to be associated with hepatitis B, diabetic nephropathy, and experimental stroke (8,(14)(15)(16). However, it remains unknown whether TIPE2 plays a role in atherosclerosis.…”
mentioning
confidence: 99%